Maximum oxygen volume profile of Unibraw 82 Malang soccer players - Budijanto Budijanto; Rubbi Kurniawan; Ratno Susanto (Sriwijaya Journal of Sport, 2022)
The purpose of this study was to find out the maximum oxygen volume level (VO2max) in Unibraw 82 Malang soccer players. Research uses a type of quantitative descriptive research with survey techniques. The study sample was 21-person Unibraw 82 Malang soccer players. The instrument used is a Multistage Fitness Test. The results of the study obtained that the lowest VO2max value owned by Unibraw 82 Malang soccer players was 27.6 ml/kg/min, while the highest VO2max value was 54.1 ml/kg/min. The average VO2max value of Unibraw 82 Malang soccer players is 39.2 with a data variation of 55.6 and a raw deviation of 7.5. Based on the results of research that has been done, it can be concluded that the VO2max level of Unibraw Malang soccer players as many as 10% of players fall into a good category, 14% of players fall into a sufficient category, 29% of players fall into a low category and 48% of players fall into a very low category.